RETRACTED: Electrospun Ta-MOF/PEBA Nanohybrids and Their CH4 Adsorption Application - Jasim, Saade Abdalkareem; Hadi, Jihad M.; Jalil, Abduladheem Turki; Catalan Opulencia, Maria Jade; Hammid, Ali Thaeer; Tohidimoghadam, Mohadeseh; Moghaddam-manesh, Mohammadreza (Frontiers in Chemistry, 2022)
In this study, for the first time, biocompatible and biodegradable Ta- metal organic framework (MOF)/ Polyether block amide (PEBA) fibrous polymeric nanostructures were synthesized by ultrasonic and electrospinning routes. The XRD peaks of products were wider, which is due to the effective effect of the ultrasonic and electrospinning method on the final product. The adsorption/desorption behaviour of the nanostructures is similar to the third- type of isotherm series, which showed the mesoporous behavior for the products. The sample has uniform morphology without any evidence of agglomeration. Since the adsorption and trapping of gaseous pollutants are very important, the application of the final Ta-MOF/PEBA fibrous polymeric nanostructures were investigated for CH4 adsorption. In order to achieve the optimal conditions of experiment and also systematic studies of the parameters, the fractional factorial design has been used. The results showed that by selecting temperature: 40 °C, time duration: 35 min, and pressure: 3 bar, the CH4 gas adsorption rate is near 4 mmol/g. Ultrasonic and electrospinning route as well as immobilization of Ta-MOF in the PEBA fibrous network affect performance the final products for CH4 gas adsorption.